DETERMINAN PENYERAPAN TENAGA KERJA DI JAWA TIMUR TAHUN 2017-2021 - Putra, Muhammad Kevin Kurnia; Arif, Muhammad (JPEKBM (Jurnal Pendidikan Ekonomi, Kewirausahaan, Bisnis dan Manajemen), 2023)
Absorption of labor is one of the factors that can affect economic growth because high absorption of labor indicates a decrease in the existing unemployment rate and reduces the risk of poverty. This study pays attention to the effect of regional gross domestic product, human development index, district minimum wage, and population on employment in East Java during the 2017-2021 period by using a regression analysis panel data. Based on research, it shows that the human development index variable has a positive and significant influence on employment. Meanwhile, the GRDP, UMK, and POP variables do not have a significant effect on employment